2020
DOI: 10.1002/mde.3245
|View full text |Cite
|
Sign up to set email alerts
|

Internationalization and product innovation in ASEAN: The moderating role of organizational innovation

Abstract: This study investigates whether an internationalization strategy affects product innovation in ASEAN. In addition, we examine whether organizational innovation moderates the internationalization's effects on product innovation in Association of South East Asian Nation (ASEAN). The empirical analysis is performed using data from the World Bank's Enterprise Surveys and different novel ordinal regression models as well as the propensity score matching (PSM) technique to partially address the endogeneity concern. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 117 publications
(196 reference statements)
0
10
0
Order By: Relevance
“…Internationalisation is a lengthy and incremental process in which ventures gradually acquire knowledge to expand their business to distant foreign markets (Bahl et al ., 2021; García-García et al ., 2017). Besides, export firms in emerging markets fundamentally differ from the developed market, which typically leverages and exploits their ownership-specific competitive advantages in foreign markets (Autio et al ., 2000; Nguyen-Van and Chang, 2021). As a result of their proprietary, knowledge-based resources, emerging market firms outperform others in the global marketplace (Orero-Blat et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Internationalisation is a lengthy and incremental process in which ventures gradually acquire knowledge to expand their business to distant foreign markets (Bahl et al ., 2021; García-García et al ., 2017). Besides, export firms in emerging markets fundamentally differ from the developed market, which typically leverages and exploits their ownership-specific competitive advantages in foreign markets (Autio et al ., 2000; Nguyen-Van and Chang, 2021). As a result of their proprietary, knowledge-based resources, emerging market firms outperform others in the global marketplace (Orero-Blat et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it is contingent upon the frequency with which knowledge is integrated and the numerous external knowledge sources (Grant, 1996). Organisational learning might be a driver of internationalisation's positive effect on a firm's SE (Nguyen-Van and Chang, 2021).…”
Section: Degree Of Internationalisation and Strategic Entrepreneurshi...mentioning
confidence: 99%
“…Source: The World Bank (2020). (Harsanto & Firmansyah, 2023;Harsanto & Permana, 2019;Nguyen-Van & Chang, 2021). Therefore, examining the relationship between such internationalization modes and innovation outcomes in ASEAN is an interesting research topic.…”
Section: Research Contextmentioning
confidence: 99%
“…The previous studies have explained the different antecedents of organizational innovation; these include transformational leadership (Gumusluoğlu and Ilsev, 2009), social capital and weak ties (Hauser et al ., 2007), strategic partnership (Jamali et al ., 2011), project team communication (Lievens and Moenaert, 2000), interorganizational networking (Verma and Zoumpa, 2012), entrepreneurial propensity (Radosevic and Yoruk, 2013), total quality management (Bon and Mustafa, 2013), cultural factors (Tajeddini and Trueman, 2012), knowledge sharing behavior of employees (Lin, 2007), teamwork cohesion and support leadership (Lloréns Montes et al ., 2005). Some other recent studies demonstrated the effect of workforce diversity, inclusion practices (Chaudhry et al ., 2021), knowledge management practices (Khan and Zaman, 2021), internationalization (Nguyen-Van and Chang, 2021), employee training and creativity (Chaubey et al ., 2021) on organizational innovation. However, the current research pays little attention to the role of transformational and transactional leadership simultaneously on organizational innovation through mediational mechanisms.…”
Section: Literature Reviewmentioning
confidence: 99%